Hymenagaricus pakistanicus (Agaricaceae, Agaricales), a new species from Pakistan based on morphological and molecular evidence - Farid Syed, Mahrukh; Saba, Malka; Mukhtar Chattha, Seratt; Hosen, Md. Iqbal (Phytotaxa, 2023)
Hymenagaricus pakistanicus, a new taxon of the family Agaricaceae from District Karak, is described based on morphology and molecular phylogeny. It is characterized macroscopically by a broad flat pileus with squamules located in the center along with some minute scattered squamules towards the margin, and microscopically by yellowish brown basidiospores. Additionally, the striate margin and absence of an annulus distinguish H. pakistanicus from other known taxa of Hymenagaricus. The new species forms a separate independent clade within Hymenagaricus in the phylogenetic analysis further supporting its uniqueness. We present the new species with illustrated morphological description and comparison with closely related taxa. Previously, only one species of this genus, H. alphitochrous, had been reported from Pakistan.